From Policy to Classroom: A Strategic Approach to Scaling Skills-Based Learning in Secondary Education - Wasila, Siti; Arifin, Zainal; Wahidah , Finadatul (CV. Bimbingan Belajar Assyfa, 2026)
The global shift toward skills-based education necessitates a profound transformation in school-level strategic management to ensure successful curriculum implementation. This study investigates how Tanyong Mas School in Narathiwat, Thailand, bridges the gap between educational policy and classroom practice through a strategic institutional framework. Utilizing a qualitative case study methodology, data were collected through in-depth interviews, observations, and comprehensive document analysis involving principals, educators, and students. The research identifies that school leadership effectively facilitates pedagogical innovation by integrating 21st-century competencies into diverse subjects, including religious and cultural curricula. The findings demonstrate that success in scaling skills-based learning is driven by a systematic alignment of strategic planning, teacher professional agency, and the contextualization of instructional design to meet evolving learner needs. Furthermore, the study reveals that leadership commitment to fostering an adaptable ecosystem is critical for overcoming systemic challenges in curriculum modernization. The results imply that institutional leaders must act as instructional architects, shifting from top-down administration to a decentralized, inquiry-based approach that empowers teachers to innovate. Ultimately, this research provides a scalable framework for secondary institutions aiming to enhance student workforce readiness while maintaining academic integrity in a rapidly changing educational landscape.